Relaxation to one-dimensional postglottal flow in a vocal fold model - Sciamarella, Denisse (2015)
Postglottal flow in low-order dynamical systems modeling vocal fold motion is customarily considered one-dimensional. A relaxation distance is however mandatory before the flow effectively complies with this approximation. A continuous vocal fold model is used to show that this relaxation distance can impact voice simulation through the coupling strength between source and tract. The degree of interaction raises if relaxation occurs closer to the glottis, introducing complexity in the response of the system.